The feasibility of field collected pig oronasal secretions as specimens for the virologic surveillance of Japanese encephalitis virus - Chiou, Shyan-Song; Chen, Jo-Mei; Chen, Yi-Ying; Chia, Min-Yuan; Fan, Yi-Chin (PLOS Neglected Tropical Diseases, 2021)
Author summary Mosquito-borne Japanese encephalitis virus (JEV) has either endemic or seasonal patterns of transmission in Asia and Australia. Most hosts infected by the virus remains asymptomatic but can result in severe encephalitis in humans and horses, and abortion or stillbirth in pregnant sows. Isolation of virus in adult mosquitoes or pig seroconversion has been used as an early indicator of upcoming JE outbreak in humans. Genotype identification of the virus is important since current human and domestic animal vaccines are all genotype III (GIII) specific. GIII vaccine elicited immunity has reduced cross-protections to genotypes other than GIII. Our virologic surveillance using pig’s oronasal secretion detected higher prevalence and earlier genotype I virus activity than using pig’s blood and mosquitoes, respectively. This proposed surveillance tool might be more effective that will allow the public health agency to properly implement the preventive measures, such as implementing mosquito control, encouraging booster vaccination, and encouraging the use of mosquito repellent, to reduce the impact of upcoming outbreak. Collection of pig’s oronasal secretion is non-invasive to pigs and less technically demanding to operators. Thus we propose the use of pig’s oronasal secretions as the novel source of specimens for virologic surveillance to replace the traditional pig blood or adult mosquito specimens to monitor and control JE outbreak/epidemic in the future.